SISTEM AKUNTANSI PENERIMAAN KAS PADA CV.SINAR PASUNDAN - -, Abdul Gani (EKONOMIA, 2014)
Target of this research, (1) To know cash inflow accounting system  CV.SINAR Pasundan, (2) To know system internal control of cash  CV.SINAR Pasundan. Method which is used in this research is percentage having the character of korelatif. Free variable and tied at this research of environment is system internal control of cash. This research is conducted by in CV.SINAR Pasundan in June 2013. Data collecting of research of this data propagated enquette mengunakan at all employees of  Sinar Pasundan. Technique analyse data use descriptively of data, prerequisite test analyse and hypothesis test. Conclusion of this research that is existence of good enough internal control in acceptance and pengeluaraan of relied on cash is organization chart depicting dissociation of function, so that can be concluded that system internal control of cash executed by Sinar of Pasundan adequate enough (43,93%) Keyword : cash inflow accounting system